Product Differentiation and Monopolistic Market Competition in the Retail Coffee Industry in Indonesia: A Review of Sharia Compliance and Its Impact on Consumer Choices - Feby Nurbaeti; Muhammad Affandi; Rahmat Safri; Titania Mukti (Dinamis : Journal of Islamic Management and Bussiness, 2025)
The modern coffee industry in Indonesia has grown rapidly with the emergence of popular brands such as Kopi Kenangan, Janji Jiwa, and Fore Coffee. These brands operate in a monopolistic competition market structure, characterized by many sellers offering similar but differentiated products. This study aims to analyze the market structure, differentiation strategies, and the nature of competition among leading coffee brands, as well as to examine their alignment with Islamic economic principles, such as fairness, transparency, and the prohibition of unhealthy competition. This research employs a descriptive qualitative method by collecting secondary data and conducting limited interviews with consumers and business actors. The results indicate that while the competition is generally fair, aggressive promotional strategies and market dominance by larger brands may create imbalances that warrant further ethical evaluation from an Islamic economic perspective.